Resonant Converter for Ozone Generation with Digital Control - Alburqueque, Marlon J.; Tisza, Juan F.; Quispe, Brajhan B. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper presents the design of a 5kV peak, 20kHz AC power supply, which is applied to a set of discharge chambers used in ozone generation applications. The power supply is composed of two stages: a PFC Flying-Capacitor Boost, in charge of generating a stable DC bus, and a Resonant Phase-Shift Full-Bridge inverter, in charge of generating high voltages to be applied in the chambers. Likewise, the necessary relationships are presented to guarantee the operation of the proposed resonant converter, the digital control of the converter stage and the simulation results for its validation and verification.
Keywords: Flying-Capacitor; Ozone generation; Phase-Shift; Soft switching